2010
DOI: 10.1007/s00394-010-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloudy apple juice protects against chemical-induced oxidative stress in rat

Abstract: Phytochemicals in commonly consumed apple juice may protect some macromolecules against oxidative insult induced by xenobiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
5
11
0
1
Order By: Relevance
“…Apple and their derivatives have shown important antioxidant activity [33,34] due to the presence of flavonoids (catechins, flavonols, quercetin), phenolic acids (quercetin glycosides, catechin, epicatechin, procyanidins), vitamins and fibers [15], which have been described as contributors to human health against cardiovascular diseases, asthma and pulmonary dysfunction, diabetes, obesity and cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…Apple and their derivatives have shown important antioxidant activity [33,34] due to the presence of flavonoids (catechins, flavonols, quercetin), phenolic acids (quercetin glycosides, catechin, epicatechin, procyanidins), vitamins and fibers [15], which have been described as contributors to human health against cardiovascular diseases, asthma and pulmonary dysfunction, diabetes, obesity and cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention from oxidative stress plays a beneficial role in the development of many process related to free radical production such as degenerative diseases and mutagenesis or the action of certain drugs whose metabolism induces the formation of reactive oxygen species. The intake of a diet rich in antioxidant compounds can prevent some oxidative-related disorders and organ toxicity events either directly neutralizing reactive oxygen species (Kujawska et al, 2011) or modulating gene expression that contributes to oxidative stress (Soyalan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the action of this food product might be to down regulate ongoing oxidative stress and/or inflammatory processes induced by TAM, allowing for the recovery of function of cellular homeostasis. In the present experiment, we have demonstrated that the supplementation with apple snacks markedly attenuated hepatic protein and DNA oxidation induced by the xenobiotic, which is consistent with welldocumented in vitro free radical-scavenging ability and antioxidant activity of the apple products (Kujawska et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…Prevention from oxidative stress plays a beneficial role in the development of many process related to free radical production such as degenerative diseases and mutagenesis or the action of certain drugs whose metabolism induces the formation of reactive oxygen species. The intake of a diet rich in antioxidant compounds can prevent some oxidative-related disorders and organ toxicity events either directly neutralizing reactive oxygen species (Kujawska et al, 2011) or modulating gene expression that contributes to oxidative stress (Soyalan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%